Fuzzy AHP-SCOR approach for supplier evaluation and selection in medical facilities / Mohamad Khairul Eman Sofian & Muhammad Syahir Izzuddin Md Shokri - Sofian, Mohamad Khairul Eman; Md Shokri, Muhammad Syahirizzuddin (2019)
Nowadays, medical supplies are very important in our lives as new illnesses are being discovered every day. Medical facilities serve an important purpose in providing people with affordable and trustworthy medicines. Therefore, medical facilities need to decide on the best medicine suppliers to obtain the best supplies. This paper suggest a combination techniques of Fuzzy Analytical Hierarchy Process (FAHP) together with Supply Chain Operation Reference (SCOR) model to develop a new decision support system to these facilities. The main stages in supplier selection process includes data gathering, FAHP calculation, SCOR evaluation and implementation of decision making. Medical facilities which implement this method will gain benefits and competitive advantage providing their decision makers are exposed to this approach in future decision support system.